English Registers of Hotels’ Signage in Surabaya - Tafuzi, Novta Ittaqy; Susanto, Fajar (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
This study focuses on the concept of register in sociolinguistics and its relevance to the study of language usage in different domains. Registers represent specific language varieties associated with particular professional or social groups, characterized by distinct vocabulary and sentence structures. The study specifically is to identify the different registers used in hotel signage. In order to describe these registers, a qualitative descriptive research method was employed, as the data consisted of words, phrases, and long expressions extracted from hotels’ signage in Surabaya. The data were analyzed using descriptive analysis and semantic analysis, with a particular focus on Lexical Relations. The findings of the research revealed that the signage in Surabaya hotels can be categorized into two groups: Limited Envelope Register and Open Envelope Register. This study fills a gap in existing literature by providing a comprehensive analysis of the linguistic features and variations that characterize hotel signage, shedding light on the specific language choices and patterns employed in this context. The findings contribute to our understanding of sociolinguistic aspects within the hotel industry and the role of registers in language usage.